Resource partitioning and productivity of perennial pigeonpea/groundnut agroforestry systems in India - Marshall, Fiona M. (1995)
The productivity of two spatial arrangements of a perennial pigeonpea/groundnut agroforestry system was examined in relation to the capture and use of light and water and alterations in microclimatic conditions. Line planted (5.4 m alleys) and dispersed arrangements (1.8 x 1.2 m spacing) of pigeonpea were compared, using populations of 0.5 plants m2 for pigeonpea and 33 plants m2 (0.3 x 0.1 m spacing) for groundnut in both treatments. Sole pigeonpea and groundnut treatments were included for comparison.